PERAN KEGIATAN JUM’AT AGAMIS DALAM MENINGKATKAN SPIRITUALITAS DI SEKOLAH MENENGAH KEJURUAN - Ummu Salma Nur Tsania; Jumari Jumari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Religious activities in schools are a strategic effort to shape character and enhance students' spirituality. This article discusses the role of